This Ain't No Place for No Hero: Prevalence and Correlates of Representations of Victims, Helpers, and Perpetrators During the Time of National Socialism in German Families. (April 2021) - Rees, Jonas H.; Papendick, Michael; Zick, Andreas
The transmission of national history in general and family narratives in particular is prone to censorship and bias, protecting or enhancing social identities. The authors propose that, as has been shown for national groups, families also create and pass on representations about their roles and behaviors through history. In a representative survey, 1000 German respondents estimated the percentages of victims, perpetrators, and those who helped potential victims during the time of National Socialism to be 35%, 34%, and 16%, respectively. For family representations, the percentages shifted toward helping (29%) and away from complicity (20%), while representations of victimhood were as prevalent (36%) as estimates for the general population. Systematic differences suggested an alignment of general social representations of history with family representations. Participants reporting a perpetrator family representation held more positive attitudes toward refugees coming to Germany today than participants who did not report such a representation. This link was mediated through differences in societal representations. The authors discuss family representations as an intermediate, more proximate prescriptive background and points of reference, according to which more general historical representations on a national level may be aligned, and individual present-day political attitudes and behaviors oriented.